Gain-scheduled static output feedback control for saturated LPV systems with bounded parameter variations. (March 2018) - Nguyen, Anh-Tu; Chevrel, Philippe; Claveau, Fabien
Abstract: This paper presents a new design method for gain-scheduled static output feedback (SOF) controllers of saturated LPV (linear parameter varying) systems. Our solution is based on a special SOF scheme in conjunction with specific congruence transformations. The regional design is established through an effective treatment of nonlinear effects introduced by the saturations in the closed loop. Using parameter-dependent Lyapunov functions, the control design is reformulated as a parameter-dependent LMI optimization with a single line search parameter. Then, by an equivalent polytopic transformation, tractable design conditions are derived for constrained LPV systems with a broad class of parametric dependencies. In particular, it is proved that the new method generalizes some well-known results based on linear matrix equalities while reducing the design conservatism. Moreover, explicit rank constraints on state–space system matrices are not required. A physically motivated example is given for illustration purposes.